The Global Impact of COVID-19: Historical Development, Molecular Characterization, Drug Discovery and Future Directions - Aboagye Kwarteng Dofuor; Naa Kwarley-Aba Quartey; Angelina Fathia Osabutey; Belinda Obenewa Boateng; Hanif Lutuf; Joseph Harold Nyarko Osei; Selina Mawunyo Ayivi-Tosuh; Albert Fynn Aiduenu; William Ekloh; Seyram Kofi Loh; Maxwell Jnr Opoku; Owusu Fordjour Aidoo (SAGE Publishing, 2023)
In December 2019, an outbreak of a respiratory disease called the coronavirus disease 2019 (COVID-19) caused by a new coronavirus known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) began in Wuhan, China. The SARS-CoV-2, an encapsulated positive-stranded RNA virus, spread worldwide with disastrous consequences for people's health, economies, and quality of life. The disease has had far-reaching impacts on society, including economic disruption, school closures, and increased stress and anxiety. It has also highlighted disparities in healthcare access and outcomes, with marginalized communities disproportionately affected by the SARS-CoV-2. The symptoms of COVID-19 range from mild to severe. There is presently no effective cure. Nevertheless, significant progress has been made in developing COVID-19 vaccine for different therapeutic targets. For instance, scientists developed multifold vaccine candidates shortly after the COVID-19 outbreak after Pfizer and AstraZeneca discovered the initial COVID-19 vaccines. These vaccines reduce disease spread, severity, and mortality. The addition of rapid diagnostics to microscopy for COVID-19 diagnosis has proven crucial. Our review provides a thorough overview of the historical development of COVID-19 and molecular and biochemical characterization of the SARS-CoV-2. We highlight the potential contributions from insect and plant sources as anti-SARS-CoV-2 and present directions for future research.